Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Perusahaan Senopati - Yudha Sitio; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
Changes in workload carried out by PT Senopati for employees have caused a decrease in employee performance in recent times. This study attempts to reveal the effect of workload and work motivation on employee performance at PT Senopati. This study uses a quantitative approach by distributing questionnaires to 58 respondents using a survey method. The analysis of this research is generated from multiple linear regression test to test the hypothesis. The results of this study indicate that the variable workload and work motivation partially affect employee performance. The two independent variables also have a simultaneous effect on employee performance by 58%.